2006
DOI: 10.1016/j.ijsolstr.2005.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Toughening under non-uniform ferro-elastic domain switching

Abstract: The existing models of switch-toughening seldom consider the effect of non-uniform ferro-elastic domain switching in the vicinity of a crack. To explore this issue, an evolution law for the volume fraction of the switched portion under applied electromechanical loading is established from the minimum energy principle. Based on this law, a switching model capable of dealing with the non-uniform distribution of switching strain is developed. The domain switching zone is divided into a saturated inner core and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The domain switching strain of the domain switching tail region would cause additive volume force i T existing on a small thin layer of the boundary of the domain switching zone model (Reece and Guiu, 2001;Reece and Guiu, 2002;Cui and Yang, 2006): The domain switching strain of the domain switching tail region would cause additive volume force i T existing on a small thin layer of the boundary of the domain switching zone model (Reece and Guiu, 2001;Reece and Guiu, 2002;Cui and Yang, 2006):…”
Section: Theoretical R Curvementioning
confidence: 99%
See 1 more Smart Citation
“…The domain switching strain of the domain switching tail region would cause additive volume force i T existing on a small thin layer of the boundary of the domain switching zone model (Reece and Guiu, 2001;Reece and Guiu, 2002;Cui and Yang, 2006): The domain switching strain of the domain switching tail region would cause additive volume force i T existing on a small thin layer of the boundary of the domain switching zone model (Reece and Guiu, 2001;Reece and Guiu, 2002;Cui and Yang, 2006):…”
Section: Theoretical R Curvementioning
confidence: 99%
“…The stress intensity factor shielded by domain switching can be obtained by weight function calculation Cui and Yang, 2006):…”
Section: Theoretical R Curvementioning
confidence: 99%
“…Note that at any region only certain proportion of the domains switches in the experiments, therefore, the toughness variation related to domain switching is usually modified by multiplying a factor V 90 , which denotes the volume fraction of switched domains (Glazounov et al 2001;Jiang et al 2007Jiang et al , 2009Cui and Yang 2006). According to the experimental result of Jiang et al (2007), the observed proportion of the switched domains is about V ds ≈ 20%, which is adopted in the subsequent calculation.…”
Section: Crack Opening Displacement (Cod)mentioning
confidence: 99%
“…According to various models [26,[44][45][46] the shielding toughness of ferroelastic materials is defined by the coercive stress, achievable strain from domain switching, and elastic modulus of the unpoled material. The magnitude of the crack closure stress is influenced by the size and shape of the process zone, the level of strain mismatch between the process zone and the surrounding material, and the material stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several numerical models proposed to predict the shielding toughness due to ferroelastic domain switching [26,[44][45][46][47]. In these works ferroelasticity was assumed to be a constant volume phase transformation resulting in remanent strain perpendicular to the crack face.…”
Section: Discussionmentioning
confidence: 99%